FAILURE ANALYSIS OF FLAT WAGON 54 TON (GD 54) STRUCTURES - Mushlih Elhafid, Muhammad
In 2015, a total of 1213 units of 54-ton flat wagons were manufactured by PT. Industri Kereta Api has officially started operating in Indonesia. Around 10% of the total 1213 flat wagons cracked at the end of 2018. In this work, some analyses were conducted to investigate the causes of cracks in the flat wagon structure. The analysis conducted includes material analysis, static analysis, fatigue analysis, actual operational loads analysis, 54-ton flat wagon manufacturing analysis, and a review of metallographic test results. The material's chemical composition, hardness, and tensile tests were used for the material analysis. The material test results show that the material used in the 54-ton flat wagon construction complies with the JIS G 3106 standard. Static analysis of the flat wagon structure is conducted by modeling finite elements in the Ansys APDL software. The model is validated with stress measurements on structural static testing results. The static analysis results show that static loads do not cause the failure of the 54-ton flat wagon structure. In the fatigue analysis, the flat wagon model is complete with bogie and container models according to operational conditions. Stress measurement results on dynamic tests verify dynamic factors in fatigue analysis. The fatigue analysis result shows that the critical locations with a life estimated of fewer than four years occur at welded corner joints II.R2, II.R3, III.R2, and III.R3. These results are appropriate with the results of metallographic tests such as non-destructive testing (NDT), scanning electron microscopy (SEM), microstructure, and microstructure tests show that there are many structure failure cases at locations II.R2, II.R3, III.R2, III.R3 and the crack patterns due to fatigue loads. The data analysis of the actual weight of coal showed that there were cases of containers exceeding the design capacity of the flat wagon of 54 tons. On the other hand, flat wagon manufacturing analysis is carried out to determine the welding procedure and inspection of flat wagons. The analysis results show that the manufacturing process (welding and inspection) of the 54-ton flat wagon is appropriate to the standards and procedures applicable at PT. Industri Kereta Api.